On optimization of numerical differentiation methods for bivariate functions - Solodky , S. G.; Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 519.653 For the problem of numerical differentiation for bivariate functions with finite smoothness, the exact orders of the minimum radius of Galerkin information are found, and also a variant of the truncation method is constructed, which is optimal in the sense of the indicated quantity.